Preparation of probes which lead to the Identification genes that are differentially expressed with retinoic acid (RA) treatment in early Xenopus laevis embryos. - K.Youssef , Abdelgader (Scientific Journal of University of Benghazi, 2026)
Total RNA from both treated and untreated stage 14x.laevis embryos was extracted and analysed by DDRT-PCR. The RNA was coverted into CDNA by reverse transcription-PCR by using oligo (dT) primers and amplified by arbitrary 5'primers. The PCR products were compared side by side and analysed on 6% DNA sequencing gel and autoradiography. Plasmid DNA sequencing of cloned cDNAs were determined for one differential fragment (M-band). M-fragment sequence (279bp) which was isolated from RA-treated stage 14x.laevis cDNA was tailed with poly (A) characteristic of 3'untranslated region and no significant open reading frames were present. A search of the EMBL/Gen bank databases using FASTA program appeared that the 3'end of M-cloned (86bp) has 81% homology to the xenopus laevis cyclin-dependent kinase 2 promoter (CDK2). The reverse transcription-polymerase chain reaction (RT-PCR) analysis appears to support the idea that the quantity of M-mRNAs is increased in the presence of retinoic acid. The 279bp of M-clone was stored at -20°C to use it as a probe for screen a cDNA library in future.